1992
DOI: 10.1038/bjc.1992.213
|View full text |Cite
|
Sign up to set email alerts
|

DNA cell cycle distribution and glutathione (GSH) content according to circadian stage in bone marrow of cancer patients

Abstract: Summary DNA cell cycle distribution and glutathione (GSH) content in bone marrow were measured both at daytime and midnight over single 24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Our data suggested that the retinal expression of EPO and its receptor (EPOR), as well as subsequent Janus kinase 2 (Jak2) phosphorylations, are tightly linked to a time window after oxidative stress and in anticipation of daily light onset. This is consistent with physiological protection against daily light-induced, oxidative mediated apoptosis [Hardeland et al, 2003;Hrushesky 1985;Scheving et al, 1988;Smaaland et al, 1991;Smaaland et al, 1992].…”
Section: Neuroprotective Erythropoietin (Epo)supporting
confidence: 57%
“…Our data suggested that the retinal expression of EPO and its receptor (EPOR), as well as subsequent Janus kinase 2 (Jak2) phosphorylations, are tightly linked to a time window after oxidative stress and in anticipation of daily light onset. This is consistent with physiological protection against daily light-induced, oxidative mediated apoptosis [Hardeland et al, 2003;Hrushesky 1985;Scheving et al, 1988;Smaaland et al, 1991;Smaaland et al, 1992].…”
Section: Neuroprotective Erythropoietin (Epo)supporting
confidence: 57%
“…The behavior of DNA replication, the most readily identifiable cell cycle event in this culture system, is dynamically similar to the circadian time-scale gating seen in animal model systems (35) and humans (36) where a correlation between glutathione levels and circadian gating of cells into S phase has been observed (36). The role of reactive oxygen intermediates and the cellular mechanisms preventing damage to single-stranded DNA during replication have been extensively studied (37,38).…”
Section: Temporal Organization Of Functionally Related Transcriptsmentioning
confidence: 95%
“…Mean bone-marrow DNA synthesis was higher at 12:00 hr than at midnight in 11 patients with advanced malignancies; interestingly, individual midday peaks were not found in 4 patients with suppressed or inverted cortisol circadian rhythm (Smaaland et al, 1992). In a group of 11 patients with advanced cancer, circadian rhythms in urinary volume and oral temperature were validated (Hrushesky et al, 1982).…”
Section: Healthy Tissuesmentioning
confidence: 98%